Increasing the Reliability of Distribution Systems By Utilizing Mobile Transformer Units - Multi, Abdul; Cahyadi, Muhammad Rijal (Green Publisher, 2025)
Maintenance of electrical installations continues to be carried out in maintaining reliability of continuity of electricity distribution. Distribution transformer maintenance activities are carried out in a state without voltage. Of course, with condition without voltage, it has an impact on power outages which can reduce reliability value of the distribution system. In 2024, PT PLN (Persero) UP3 Cempaka Putih has carried out transformer maintenance activities at 7 distribution substations with an average outage duration is 155 minutes. At Distributon Substation TP117, transformer maintenance has been carried out using a minimal outage method, namely by utilizing Mobile Transformer Units as mediator for temporary load transfer during maintenance. Total duration of the outage was only 44 minutes with value of SAIDI is 0.035 minutes/customer and value of ENS is 245,084.07 Wh. By calculating the SAIDI and ENS values based on the pure duration of maintenance work, SAIDI value is calculated to be greater, amount 0.102 minutes/customer and the ENS value is 708,515.77 Wh. So it can be determined that the potential reduction for SAIDI value is 65.69% and ENS value is 65.41%. This means that the reliability of the distribution system can increase because the SAIDI and ENS values can be reduced.